Chapter Challenges and New Frontiers in the Paediatric Drug Discovery and Development - Bonifazi, Donato (InTechOpen, 2020)
Drug discovery and development advances in the last decades allowed to find a treatment for many preventable diseases. However, all too often, children are excluded from these progresses since most of the new medicines have been discovered and developed for the adult population. Even if paediatricians routinely give drugs to children 'off-label', researchers have demonstrated that children do not respond to medications in the same way as adults. Furthermore, certain specific disorders are unique to children or occur in children differently than in adults. Besides specifically testing medicines in children in proper clinical studies taking into due account the peculiarity of this population, there is a growing recognition of the need to develop paediatric medicines having in mind the specificities of this vulnerable population. In this chapter, we will provide an overview on the drug discovery and development path for children highlighting challenges and new frontiers of each phase from the discovery to the preclinical and clinical development as well as we will provide a slightest hint about paediatric biomarkers discovery, age-appropriate formulation, pregnancy, and perinatal pharmacology and in silico pharmacology. Finally, pricing and reimbursement policies for medicines and new and existing research initiatives in the field will be discussed.